2002
DOI: 10.1074/jbc.m203659200
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Monomer-Dimer Equilibrium of Bovine β-Lactoglobulin by Amino Acid Substitution

Abstract: Bovine ␤-lactoglobulin, a major protein in cow's milk composed of nine ␤-strands (␤A-␤I) and one ␣-helix, exists as a dimer at neutral pH while it dissociates to a native monomer below pH 3.0. It is assumed that the intermolecular ␤-sheet formed between I-strands and salt bridges at AB-loops play important roles in dimer formation. Several site-directed mutants in which intermolecular interactions stabilizing the dimer would be removed were expressed in the methylotrophic yeast Pichia pastoris, and their monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
75
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 25 publications
9
75
1
1
Order By: Relevance
“…As was also shown in our previous papers (12,14), the far-UV CD spectrum of wild-type ␤-lg at pH 7.0 had a minimum at 218 nm with an ellipticity of Ϫ6000 (Fig. 2a), showing that it is a predominantly ␤-sheet protein (Fig.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…As was also shown in our previous papers (12,14), the far-UV CD spectrum of wild-type ␤-lg at pH 7.0 had a minimum at 218 nm with an ellipticity of Ϫ6000 (Fig. 2a), showing that it is a predominantly ␤-sheet protein (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…The quantity of protein expressed was checked with SDS-PAGE, and one of the strains with the highest level of expression was selected for every mutant and adopted for subsequent mass culture in a 1-liter jar fermenter. For wild-type ␤-lg, we used the strain constructed previously and stored as glycerol stock (12). The broth of mass culture was centrifuged, and the supernatant was filtered with 5.0-m-pore size Millex-SV (Millipore, Bedford, MA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although BLG is dimeric at neutral pH, it dissociates into monomers at low pH and very low ionic strength condition because of intermolecular electrostatic repulsions. 2,3 However, the monomers retain their tertiary structures at acidic pH. Both crystal [4][5][6][7][8][9] and solution 10,11 structures of BLG show that the monomer contains nine b-strands (strands A-I), an ahelix, and three short 3 10 helices.…”
mentioning
confidence: 99%
“…A mutational study has shown that salt bridges between Asp33 and Arg40 of the opposing AB-loops that are important to the stability of the dimer. 3 BLG binds a variety of hydrophobic compounds including retinol, fatty acids, and vitamin D 3 at its hydrophobic cavity inside the barrel. [12][13][14] The loop between the E-and F-strands (EF-loop) obstructs the entrance to the b-barrel in the crystal structure at pH ¼ 6.2, whereas the entrance is open at pH ¼ 7.1.…”
mentioning
confidence: 99%